2011
DOI: 10.2741/e241
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expansion of adipose-derived stem cells for tissue engineering

Abstract: For treatment of cardiac failure with bone marrow-derived mesenchymal stem cells, several clinical trials are ongoing. However, more attention is gathering on the use of adipose tissue-derived stem cells (ASCs). This paper describes the optimization of isolation and propagation of ASCs for subsequent clinical use. In the isolation step, several enzymes were compared with respect to yield of nucleated cells and precursor cells. Our results showed, that the interdonor variablility was greater than differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…For example, the self-renewal of human ESCs is best maintained in 5% oxygen, 13,14 while that of limbal stem cells at 2%. 16 With respect to ASCs, our own comparative studies identified 5% oxygen in culture atmosphere as optimal to support growth, [22][23][24] although it is possible that in certain settings, even lower oxygen concentrations may prove useful. 47,48 The somewhat disparate experimental evidence clearly indicates that better standardization of hypoxic experiments together with identification of possible pitfalls is necessary before consensus on a widely accepted value can be reached.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, the self-renewal of human ESCs is best maintained in 5% oxygen, 13,14 while that of limbal stem cells at 2%. 16 With respect to ASCs, our own comparative studies identified 5% oxygen in culture atmosphere as optimal to support growth, [22][23][24] although it is possible that in certain settings, even lower oxygen concentrations may prove useful. 47,48 The somewhat disparate experimental evidence clearly indicates that better standardization of hypoxic experiments together with identification of possible pitfalls is necessary before consensus on a widely accepted value can be reached.…”
Section: Discussionmentioning
confidence: 97%
“…22,24,25 Three lines of ASCs, designated ASC12, 21, and 23, which have been isolated and characterized previously, 23 were continually grown in standard growth conditions involving an alpha-modified Eagle medium (A-MEM; Invitrogen, Carlsbad, CA) supplemented with 10% FCS (Europa Bioproducts Ltd., Cambridge, United Kingdom), 100 IU/mL penicillin, 100 mg/ mL streptomycin, and 50 mg/mL gentamicin or in defined and xenogeneic-free conditions involving the StemPro Ò MSC SFM XenoFree + CELLstart Ô culture system (StemPro) (all from Invitrogen). The essential feature of StemPro medium is that it is supplemented with a platelet-derived growth factor, transforming growth factor (TGF)-b, and fibroblast growth factor.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Adipose tissue-derived stem cells not only differentiate into osteoblastic cells (OBs) or endothelial cells (ECs), but also are obtainable in large quantities and provide an excellent cellular source for engineered constructs. [8][9][10][11] Studies in several animal models have demonstrated that the implantation of osteoprogenitor cells and OBs can improve the osteogenic and osteoinductive potential of allogenic bone, which occurs likely secondary to the production of growth factors and bone morphogenetic proteins (BMPs) that reciprocally stimulate OBs to form mineralized bone matrix. 5,[12][13][14][15] In addition, in order to improve the blood supply of such grafts, angiogenic strategies have been developed and include the direct application of angiogenic growth factors such as vascular endothelial growth factor (VEGF) and fibroblast growth factor as recombinant proteins or by gene therapeutics.…”
Section: Introductionmentioning
confidence: 99%